ANALISIS KUALITATIF PADA BATU KECUBUNG KOPI MENGGUNAKAN LIBS - Kusuma Dewi, Ida Ayu Gede; Suyanto, Hery; Alit Paramarta, Ida Bagus; Suastika, K. (BULETIN FISIKA; Vol 17 No 2 (2016): BULETIN FISIKA, 2016)
It has been conducted research on the qualitative analysis on amethyst coffee using LIBS.This study aims to determine the content of the element in amethyst coffee that can later be used as a comparison or reference further research in the elemental analysis amethyst coffee. With treatment, the laser irradiated amethyst coffee at 100 mJ, and the data retrieved by the accumulation of 3, delay time 1 µs and repetition as much as 3 points in different areas of each region analysis of depth function (Depth Profile) with 60 times the laser irradiation. The main element as a constituent amethyst Coffee is silicon (Si), Sodium (Na), calcium (Ca), potassium (K) and oxygen (O2), while the element on its outer surface is iron (Fe) and phosphorus (P) were analyzed using LIBS.